Integration of Financial Literacy into Contextual Mathematics Learning through Project Based Approach: A Case Study in Sixth Grade Of Elementary School - Duwi Purwanti; Rosidah Aliim Hidayat (Jurnal Ilmiah Sekolah Dasar, 2025)
Many elementary students struggle to connect mathematical concepts with real-life financial situations, limiting their ability to make informed financial decisions. Mathematics instruction at this level often lacks socio-economic relevance, making it less meaningful for learners. This study aims to analyze and describe the integration of financial literacy into contextual mathematics learning through the Project-Based Learning (PjBL) model, enriched by the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach and Tri-N values (Niteni, Nirokke, Nambahi). Employing a descriptive qualitative approach, the research involved sixth-grade students and a classroom teacher. Data were collected through participatory observation, semi-structured interviews, documentation of student projects, and assessments of student attitudes, and were analyzed thematically. The results show that the “Masak Pintar” project enhanced students’ understanding of mathematical concepts, improved budgeting skills, and fostered character values such as responsibility, empathy, and honesty. The STEAM approach enriched the learning process through interdisciplinary integration, while the Tri-N philosophy strengthened reflective learning grounded in local cultural values. This study concludes that the integrated learning model is an effective and innovative strategy for holistically developing students’ academic competence, financial skills, and 21st-century competencies at the elementary school level.